The Development of a Scientific-based Academic Supervision Management Model - Rokhman Rokhman; Nirva Diana; Yurnalis Etek; Koderi Koderi; Muhammad Sufian (AL-ISHLAH: Jurnal Pendidikan, 2024)
The role of supervision in education is crucial for fostering teacher professionalism, necessitating a supervision model tailored to teachers' needs. The current supervision models often fall short of meeting these needs and lack efficacy and efficiency. This study aimed to devise a scientific-based academic supervision management model, evaluate its viability, and determine its impact on supervisor competency in terms of effectiveness and efficiency. Using the ADDIE model, a scientific-based academic supervision management model was crafted. Data were gathered through observation, questionnaires, and documentation, involving principals and supervisors in Tulang Bawang Regency. A mixed-methods approach was applied for data analysis. The developed model, encapsulating the principles of Observing, Questioning, Experimenting, Associating, and Communicating (OQEAC), underwent evaluation by experts in content, language, and media, and was found suitable for field testing. Subsequent trials with principals and supervisors in both small and large groups affirmed the model's high effectiveness and its capability to enhance supervisor competence. This research corroborates that the OQEAC model, grounded in scientific principles, significantly improves education supervisors' skills, thereby elevating teaching and learning quality. The OQEAC-based academic supervision represents a potent strategy for augmenting educational quality and empowering teachers to lead learning outcome improvements.